2019
DOI: 10.6018/rc-sar.22.1.354351
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la Influencia de la Función de Auditoría Interna sobre las Cuotas de Auditoría

Abstract: The aim of this paper is to analyse the relationship between the internal audit function and auditor's fees using a sample of Spanish listed companies between 2003 and 2011. We use the audit fees model that was proposed by Simunic (1980). Our results indicate that fees are greater in those companies that have an internal audit function. In addition, if there are meetings between the audit committee and the internal audit function, this is statistically significant with audit fees. This paper contributes to lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
(65 reference statements)
0
9
0
1
Order By: Relevance
“…From the examination, it is suggested that one of the proxies of the internal audit function, namely the size of internal audit personnel within the firm, increases audit fee. Similarly, a study from Sierra-García et al . (2019) revealed that a good-quality internal audit function has a significant positive relationship with audit fees.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 73%
See 4 more Smart Citations
“…From the examination, it is suggested that one of the proxies of the internal audit function, namely the size of internal audit personnel within the firm, increases audit fee. Similarly, a study from Sierra-García et al . (2019) revealed that a good-quality internal audit function has a significant positive relationship with audit fees.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 73%
“…The contribution of the internal audit function strengthens a significant negative relationship between the good-quality internal audit function and the audit fee. Likewise, a study conducted by Sierra-García et al . (2019) found that audit fees increased significantly when the firm had an internal audit function.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 84%
See 3 more Smart Citations